PEMBERDAYAAN MASYARAKAT DALAM PENGGUNAAN JERUK NIPIS SEBAGAI ANTIHIPERLIPIDEMIA DI KELURAHAN COBLONG KECAMATAN CIPAGANTI - Lilis Febriyanti; Elvi Trinovani (Poltekkes Kemenkes Bandung, 2022)
Hypercholesterolemia has become a health problem in both developed and developing countries. The highest prevalence of hypercholesterolemia is in Europe, followed by America, and the lowest is in Southeast Asia. According to data from the World Health Organization (WHO) (2015), hypercholesterolemia has caused a third of the number of ischemic heart disease. Meanwhile, deaths reached 2.6 million people (4.5% of total deaths) and 29.7 million people experienced the inability to live a normal life. The results showed that lime (Citrus Aurantifolia) was beneficial for lowering total blood cholesterol levels at a dose of 1.5 ml/KgBB. This is because lime juice is rich in Vitamin C which is a natural anti-oxidant, which works by reducing oxidative stress, inhibiting carbohydrate digestion and inhibiting fat transport along the walls of the small intestine, thereby lowering cholesterol in the blood. So the PKM Pharmacy team did community service with the title Community Empowerment in the Use of Lime Fruit as Antihypercholesterolemia in Coblong Village, Cipaganti District, Bandung City. From the results of this community service, it was found that there was an increase in knowledge, attitudes and skills as well as an increase in the health of community partners with outreach activities from the PKM proposer team at the Bandung Health Polytechnic Department of Pharmacy regarding the use of lime fruit to overcome hypercholesterolemia problems, checking the community's total blood cholesterol levels before and after PKM program, the practice of making traditional drinks from lime fruit plants for health benefits.